2015
DOI: 10.1017/s1355617715001071
|View full text |Cite
|
Sign up to set email alerts
|

Increased Delay Discounting on a Novel Real-Time Task among Girls, but not Boys, with ADHD

Abstract: The aim of this study was to examine delay discounting in girls and boys with ADHD-Combined type (ADHD-C) relative to typically developing (TD) children on two tasks that differ in the extent to which the rewards and delays were experienced by participants. Children ages 8–12 years with ADHD-C (n = 65; 19 girls) and TD controls (n = 55; 15 girls) completed two delay discounting tasks involving a series of choices between smaller, immediate and larger, delayed rewards. The classic delay discounting task involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
59
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(78 citation statements)
references
References 73 publications
16
59
2
1
Order By: Relevance
“…Consequently, this study provides a unique contribution to the literature with regard to examining an understudied and therefore less understood question regarding the neuropsychological processes associated with variability in delay discounting task performance among girls and boys with ADHD. Furthermore, this study aimed to replicate gender-difference findings from previous work (Rosch & Mostofsky, 2016), which is essential given the relative dearth of literature explicating gender differences in reward-based decision-making in children with ADHD. It was hypothesized that (a) children with ADHD, relative to TD children, would exhibit greater delay discounting and weaker cognitive control as assessed using spatial span backwards, attention regulation, and inhibitory control tasks, (b) poor cognitive control would be related to greater delay discounting, and (c) the pattern of neuropsychological deficits and associations with delay discounting may differ for girls and boys with ADHD.…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…Consequently, this study provides a unique contribution to the literature with regard to examining an understudied and therefore less understood question regarding the neuropsychological processes associated with variability in delay discounting task performance among girls and boys with ADHD. Furthermore, this study aimed to replicate gender-difference findings from previous work (Rosch & Mostofsky, 2016), which is essential given the relative dearth of literature explicating gender differences in reward-based decision-making in children with ADHD. It was hypothesized that (a) children with ADHD, relative to TD children, would exhibit greater delay discounting and weaker cognitive control as assessed using spatial span backwards, attention regulation, and inhibitory control tasks, (b) poor cognitive control would be related to greater delay discounting, and (c) the pattern of neuropsychological deficits and associations with delay discounting may differ for girls and boys with ADHD.…”
mentioning
confidence: 89%
“…However, the majority of studies examining choice-impulsivity in children with ADHD have used choice-delay tasks (Patros et al, 2016) limiting our understanding of how children with ADHD perform on delay discounting tasks which tend to be more commonly used in the broader cognitive neuroscience literature and in studies of adult clinical populations (see reviews by Hamilton et al, 2015; Peters & Buchel, 2011). Furthermore, recent findings from a study involving two delay discounting tasks demonstrated that reward-based decision-making in children with ADHD may depend on characteristics of the task (e.g., type of reward, task duration) and/or the participant (e.g., sex; Rosch & Mostofsky, 2016), emphasizing the need for further research in this area.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Reason for exclusion Barnett et al [86] Participants are teachers Benyakorn et al [87] Not interventional Bishop [88] Intervention not technology Bonarini et al [89] Population focus not ADHD Bul et al [90] Outcome measures do not assess ADHD-related difficulties Chan et al [91] Not interventional Chen et al [92] Not interventional Christiansen et al [93] Intervention reliant on others Dale and Grut [94] Not exclusively for ADHD Duffy [95] Population focus not ADHD Enebrink et al [96] Population focus not ADHD References Reason for exclusion Epstein et al [97] Intervention reliant on health care professionals Fiellin et al [98] Population focus not ADHD Frutos-Pascual et al [99] Population focus not ADHD Frutos-Pascual and GarciaZapirain [100] Participants typically developing, not ADHD Gray et al [72] ADHD not primary diagnosis of participants Halperin et al [101] Intervention not technology Janeslätt et al [102] Intervention not technology Kim et al [103] Intervention not technology Lim et al [104] Intervention reliant on health care professionals Mazurek and Engelhardt [105] Not interventional Myers et al [106] Participants ADHD diagnosis not confirmed Nie et al [107] Intervention not technology Pandria et al [108] Not interventional Rohani et al [109] Participants ADHD diagnosis not confirmed Rosch and Mostofsky [110] Not interventional Schafer et al [111] Participants not received ADHD diagnosis Schuck et al [112] Participants not received ADHD diagnosis Shah et al 2012 Not interventional Silva et al [113] Technology as outcome measure, not intervention Steeger et al 2016 Participants ADHD diagnosis not confirmed Stephenson [114] Population focus not ADHD Tse et al …”
Section: Appendix 2: References and Reasons For Exclusionmentioning
confidence: 99%